2011
DOI: 10.1261/rna.2670811
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent labeling of tRNA dihydrouridine residues: Mechanism and distribution

Abstract: Dihydrouridine (DHU) positions within tRNAs have long been used as sites to covalently attach fluorophores, by virtue of their unique chemical reactivity toward reduction by NaBH 4 , their abundance within prokaryotic and eukaryotic tRNAs, and the biochemical functionality of the labeled tRNAs so produced. Interpretation of experiments employing labeled tRNAs can depend on knowing the distribution of dye among the DHU positions present in a labeled tRNA. Here we combine matrixassisted laser desorption/ionizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 38 publications
0
38
0
Order By: Relevance
“…After washing away unbound complexes, collection of real-time translation traces began 10 s prior to injecting 10 nM fluorescent-labeled ternary complexes, 2 μM EF-G and 2 mM GTP into the flow cell. Fluorescent-labeled ternary complexes were preformed from EF-Tu, GTP, and charged tRNAs labeled with either Cy3 or Cy5 at dihydrouridine positions in the D loop (57,58). Recording continued Fig.…”
Section: Methodsmentioning
confidence: 99%
“…After washing away unbound complexes, collection of real-time translation traces began 10 s prior to injecting 10 nM fluorescent-labeled ternary complexes, 2 μM EF-G and 2 mM GTP into the flow cell. Fluorescent-labeled ternary complexes were preformed from EF-Tu, GTP, and charged tRNAs labeled with either Cy3 or Cy5 at dihydrouridine positions in the D loop (57,58). Recording continued Fig.…”
Section: Methodsmentioning
confidence: 99%
“…5,6 Such labeling proceeds via a substitution at the THU residues to yield N -substituted tetrahydrocytidine (THC) residues within the tRNA. Previous work 6 showed that Cy3 hydrazide labeled Phe-tRNA Phe (reduced) at both positions 16 and 20 to near equal extents (relative labeling 1.0:1.2, respectively) and we assume a similar distribution is obtained for labeling of tRNA Phe (reduced) by VI . In the present case, the overall labeling stoichiometry was 0.4 V /tRNA Phe .…”
Section: Resultsmentioning
confidence: 99%
“…In this prior work, fl-tRNAs were synthesized by condensing fluorescent weak-base amines, including hydrazides, with the tetrahydrouridine (THU) residues in bulk tRNA that are formed by specific reduction of dihydrouridine (DHU) residues within the D-loops of tRNA, as described. 46 The FRET signal generated using bulk fl-tRNAs provided a measure of the rate of total protein synthesis within transfected cells. 1 …”
Section: Introductionmentioning
confidence: 99%
“…RNase T1 digestion and matrix-assisted laser desorption/ionization (MALDI) mass spectrometric analysis was performed on tRNA Ile UAU as described (18). MALDI peaks were observed corresponding to oligonucleotides present in tRNA Ile UAU but absent in the other Ile isoacceptor, tRNA Ile AAU (UALp, CUCGp, CACCAp, CUPCGp, ACC7DGp, CUPAP6ACGp).…”
Section: Methodsmentioning
confidence: 99%
“…Dihydrouridines present in bulk or purified isoacceptor tRNAs were reduced with NaBH 4 and labeled with either Rhodamine 110 (Rd110) or Cy3-hydrazide as described (16,18). The labeling efficiencies were 0.87 Rd110/bulk tRNA, 0.86 Rd110/tRNA Ile UAU , 0.68 Rd110/tRNA Gly CCC , 0.68 Cy3/bulk tRNA, 0.83 Cy3/tRNA Ile UAU and 0.48 Cy3/tRNA Pro AGG .…”
Section: Methodsmentioning
confidence: 99%